Influence of Surgical Technique on Mastectomy and Reexcision Rates in Breast-Conserving Therapy for Cancer. (16th January 2012) - Unzeitig, Alison; Kobbermann, Anne; Xie, Xian-Jin; Yan, Jingsheng; Euhus, David; Peng, Yan; Sarode, Venetia; Moldrem, Amy; Leitch, A. Marilyn; Andrews, Valerie; Rao, Roshni
Abstract : Introduction . Breast conserving surgery (BCS) requires tumor excision with negative margins. Reexcision rates of 30–50% are reported. Ultrasound localization, intraoperative margin pathology, and specimen mammography have reduced reexcisions, but require new equipment. Cavity shave margin (CSM) is a technique, utilizing existing equipment, that potentially reduces reexcision. This study evaluates CSM reexcision impact. Methods . 522 cancers treated with BCS were reviewed. Patients underwent standard partial mastectomy (SPM) or CSM. Data collected included demographics, pathology, and treatments. Results . 455 SPMs were compared to 67 CSMs. Analysis revealed no differences in pathology, intraductal component, or neoadjuvant chemotherapy. Overall reexcision rate = 43%. Most reexcisions were performed for DCIS at margin. SPMs underwent 213 reexcisions (46.8%), versus 16/67 (23.9%) CSMs ( P = 0.0003). Total mastectomy as definitive procedure was performed after more SPMs ( P = 0.009). Multivariate analysis revealed CSM, % DCIS, tumor size, and race to influence reexcisions. Conclusions . CSM is a technique that reduces reexcisions and mastectomy rates.